Asymmetric Dimethylarginine as a Biomarker in Coronary Artery Disease - Papageorgiou, Nikolaos; Theofilis, Panagiotis; Oikonomou, Evangelos; Lazaros, George; Sagris, Marios; Tousoulis, Dimitris (Current Topics in Medicinal Chemistry, 2023)
As atherosclerosis remains a leading cause of morbidity and mortality worldwide despite the advances in its medical and interventional management, the identification of markers associated with its incidence and prognosis constitutes an appealing prospect. In this regard, asymmetric dimethylarginine (ADMA), a well-studied endogenous endothelial nitric oxide synthase inhibitor, represents a core mediator of endothelial dysfunction in atherosclerotic diseases. Given the pathophysiologic background of this molecule, its importance in the most frequent atherosclerotic manifestation, coronary artery disease (CAD), has been extensively studied in the past decades. The available evidence suggests elevation of ADMA in the presence of common cardiovascular risk factors, namely diabetes mellitus, arterial hypertension, and hypertriglyceridemia, being related to endothelial dysfunction and incident major adverse cardiovascular events in these groups of patients. Moreover, ADMA is associated with CAD occurrence and severity, as well as its prognosis, especially in populations with renal impairment. Interestingly, even in the absence of obstructive CAD, increased ADMA may indicate coronary endothelial dysfunction and epicardial vasomotor dysfunction, which are prognostication markers for incident cardiovascular events. In the case of acute coronary syndromes, high ADMA levels signify an augmented risk of incomplete ST-segment elevation resolution and poorer prognosis. Abnormal ADMA elevations may indicate adverse outcomes following percutaneous or surgical coronary revascularization, such as in-stent restenosis, graft patency, and hard cardiovascular endpoints. Finally, since its association with inflammation is significant, chronic inflammatory conditions may present with coronary endothelial dysfunction and subclinical coronary atherosclerosis by means of increased coronary artery calcium, with augmented ADMA acting as a biomarker.
Keywords: Endothelial dysfunction